Development of Cold Hardy, Large Patch Resistant Zoysiagrass Cultivars for the Transition Zone - Mingying Xiang; J. Fry; M. Kennelly (Kansas Agricultural Experiment Station Research Reports, 2017)
AZ. japonicagenotype TAES 5645 which exhibited resistance to large patch in preliminary studies conducted by our collaborators at Texas A&M University was used as a breeding parent there and crossed with 22 cold hardy zoysiagrasses, resulting in 985 progeny. These progeny were evaluated for cold hardiness and agronomic traits (establishment rate, overall quality, spring greenup, leaf texture, and genetic color) in Manhattan, KS; West Lafayette, IN; and Dallas, TX; from 2012 to 2014. This report focuses on the Manhattan, KS, results. From this work, 60 progeny were identified for further evaluation in larger plots. In fall 2016, ‘Meyer’ (42% of plot area affected) had more large patch than all zoysiagrass progeny (0 to 23%). The top-performing zoysiagrass progeny had little or no large patch present. Among this group of experimental zoysiagrasses, there appear to be promising progeny that have good winter hardiness, resistance to large patch, and improved turf quality characteristics but data collection is ongoing. Kansas data will be combined with data from other sites.
Keywords: Turfgrass; disease